Measuring autophagy level along with vaccine reactive IFN-+CD4+ Th1 cells may be a promising approach to understand effi cacy of anti TB vaccine(s) - Om Parkash (Journal of Vaccines and Immunology - Peertechz Publications, 2018)
Autophagy is a homeostatic process in the eukaryotic cells which contributes towards degradation of unwanted cellular constituents, killing of the invading intracellular microbes and generation of cell mediated immunity (CMI). The professional antigen presenting cells (APCs) like: macrophages and dendritic cells, present microbial antigens (derived from engulfed and killed microbe) in combination with MHC-II to generate IFN-γ producing CD4+ Th1 cells. Over the years, inducing IFN-γ+ CD4+ Th1 mediated CMI has remained, predominantly, as the target for developing anti TB vaccine. In individuals, where Mycobacterium tuberculosis (MTB) bacilli invading the APCs evade induction of autophagy, anti TB vaccine may not be effective due to lack of presentation of MTB derived antigens to generate and re-stimulate vaccine generated memory CD4+ Th1 cells. On the other hand, induction of autophagy in the APCs kills the invading MTB bacilli and may suffi ciently present microbial antigens to generate and re-stimulate vaccine generated IFN-γ producing CD4+ Th1 memory cells. The re-stimulated memory cells then differentiate to effector CD4+ Th1 cells to release IFN-γ which further takes part in activation of antimicrobial activity in APCs thereby leading to protection of the vaccinees and sustaining the vaccine generated CMI. Keeping all these points in view, a hypothesis has been described here, wherein it has been suggested that measuring autophagy activation status in combination with prevalence of IFN-γ producing memory/effector CD4+ Th1 cells against vaccine antigens may prove to be promising biomarkers for assessing protective effi cacy of anti TB vaccine(s).